X-RAY AND ELECTRON SPECTROMICROSCOPY OF CARBON NANOTUBE SYSTEMS - Najafi, Ebrahim (My University, 2011)
This thesis presents studies of the X-ray linear dichroism (XLD) in individual single-walled (SW) and multi-walled (MW) carbon nanotubes (CNT) measured by a scanning transmission X-ray microscope (STXM). The C 1s spectra of CNT showed a large XLD at the C 1s→π* transition. The magnitude of the XLD was found to be related to the quality of CNT such that in high quality CNT, it was fairly large and as the quality lowered it decreased. This dichroic effect was used to map defects along individual CNT. In addition, STXM was employed to map chemical components in pristine, purified, and dodecyl functionalized SWCNT bundles to investigate the changes occurring in them due to chemical functionalization.
STXM has limited spatial resolution. Thus, electron energy loss spectroscopy (EELS) in a transmission electron microscope (TEM) was used to obtain similar information about CNT, but at much higher spatial resolution. The measurements performed in the scanning transmission electron microscopy (STEM) mode produced signals analogous to the XLD when the orientation of the momentum transfer (q) was resolved. This was achieved by displacing the pattern of electron scattering from CNT relative to the EELS entrance aperture. TEM-EELS was also utilized to map defects in pristine and focused ion beam (FIB) modified CNT.
Keywords: Carbon nanotube; NEXAFS; STXM; X-ray linear dichroism; momentum transfer; electron energy loss spectroscopy; Analytical Chemistry; Materials Chemistry; Physical Chemistry; Structural Materials; Analytical Chemistry